Emerging ecological trends in West Africa: implications on soil organic matter and other soil quality indicators - Samuel Ayodele Mesele; Caleb Melenya Ocansey; Amelie Bougma; Jamiu O. Azeez; Godwin A. Ajiboye; Vincent Logah; Halidou Compaore; Elmar M. Veenendaal; Jonathan Lloyd (Plant and Soil, 2024)

Soil mineralogical and nutrient characteristics of forest islands and surrounding ecosystem types in West Africa suggest anthropogenic soil improvement - Samuel A. Mesele; Caleb Melenya; Amelie Bougma; Jamiu O. Azeez; Godwin A. Ajiboye; William Dubbin; Vincent Logah; Halidou Compaore; Elmar M. Veenendaal; Jonathan Lloyd (Plant and Soil, 2024)

Soil aggregate stability of forest islands and adjacent ecosystems in West Africa - Amelie Baomalgré Bougma; Korodjouma Ouattara; Halidou Compaore; Hassan Bismarck Nacro; Caleb Melenya; Samuel Ayodele Mesele; Vincent Logah; Jamiu Oladipupo Azeez; Elmar Veenendaal; Jonathan Lloyd (Plant and Soil, 2022)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Variation in soil carbon stocks and their determinants across a precipitation gradient in West Africa - Gustavo Saiz; Michael I. Bird; Tomas Domingues; Franziska Schrodt; Michael Schwarz; Ted R. Feldpausch; Elmar Veenendaal; Gloria Djagbletey; Fidele Hien; Halidou Compaore; Adama Diallo; Jon Lloyd (Global Change Biology, 2012)

Variation in soil carbon stocks and their determinants across a precipitation gradient in W est A frica - Gustavo Saiz; Michael I. Bird; Tomas Domingues; Franziska Schrodt; Michael Schwarz; Ted R. Feldpausch; Elmar Veenendaal; Gloria Djagbletey; Fidele Hien; Halidou Compaore; Adama Diallo; Jon Lloyd (Global Change Biology, 2012)
We examine the influence of climate, soil properties and vegetation characteristics on soil organic carbon ( SOC ) along a transect of W est A frican ecosystems sampled across a precipitation gradient on contrasting soil types stretching from G hana (15° N ) to M ali (7° N ). Our findings derive from a total of 1108 soil cores sampled over 14 permanent plots. The observed pattern in SOC stocks reflects the very different climatic conditions and contrasting soil properties existing along the latitudinal transect. The combined effects of these factors strongly influence vegetation structure. SOC stocks in the first 2 m of soil ranged from 20 Mg C ha −1 for a S ahelian savanna in M ali to over 120 Mg C ha −1 for a transitional forest in G hana. The degree of interdependence between soil bulk density ( SBD ) and soil properties is highlighted by the strong negative relationships observed between SBD and SOC ( r 2 > 0.84). A simple predictive function capable of encompassing the effect of climate, soil properties and vegetation type on SOC stocks showed that available water and sand content taken together could explain 0.84 and 0.86 of the total variability in SOC stocks observed to 0.3 and 1.0 m depth respectively. Used in combination with a suitable climatic parameter, sand content is a good predictor of SOC stored in highly weathered dry tropical ecosystems with arguably less confounding effects than provided by clay content. There was an increased contribution of resistant SOC to the total SOC pool for lower rainfall soils, this likely being the result of more frequent fire events in the grassier savannas of the more arid regions. This work provides new insights into the mechanisms determining the distribution of carbon storage in tropical soils and should contribute significantly to the development of robust predictive models of biogeochemical cycling and vegetation dynamics in tropical regions.